PROSPEK PENGEMBANGAN TANANAMAN LANGKA DITINJAU DARI SIFAT ARANG DAN ASPEK LAINNYA - Sri Komarayati (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
Jackfruit (Artocarpus heterophyllus Lamk) is a multi purpose tree species. An analysis showed that Jackfruit wood contains cellulose content 56. 74%, lignin content 28.76%, pentosan content 18.64%, yield of charcoal 38.74 %, calorific value of charcoal 7108.37 cal/g and charcoal briquette has moisture content 5.10%, ash content 3.06%, volatile matter 25.51%, fixed carbon 71.23%, density 0.63 g/cm3, compression strength 350 kg/cm2 and calorific value 6487. 28 cal/g.Further study showed that Jackfruit leaf has moisture content 14.50%, ash content 5.24%, silica 3.60% , cellulose 38.83%, lignin 24.18% and pentosan 4.56%. This leaves is suitables for cattle fodder.Based on the analysis, Jackfruit wood is suitable for energy sources. Besides that Jackfruit plant can be used for export comodity, source of income and as intercropping plant which caused increasing of growth percentage of main plant upper than 85% and can increase 15 -20% of income of forest farmer (tumpang sari participant).